Is there a role for professional associations in fostering research? - Smith, Kerry; Harvey, R. (School of Communication & Information, Nanyang Technological University, 2006)
Throughout the world professional associations in librarianship place considerable emphasis on the professional credentialing of their members. This normally means that educational and training courses of study offering a first professional qualification take up much of this activity. Since this first professional qualification does not normally require emphasis on the research process, but rather in obtaining the required skills and knowledge in order to practice librarianship, it is little wonder that the role of research in the profession has not always been openly encouraged by its associations. Nevertheless, there is evidence that some associations are realizing that research and the research process needs to be better recognized, particularly as library professionals are increasingly undertaking higher level qualifications which include a research component. Yet if a research qualification is not always necessary for recognition as a professional librarian, the question needs to be asked: why should librarians bother to undertake the rigours of study to achieve it? The paper will discuss the importance or otherwise of research and its processes in the profession of librarianship and consider the role of the professional association in recognizing, enabling and promoting a research culture amongst qualified professionals. The paper will particularly address the Australian context.